(untitled) (Beacon: International Journal of Education and Social Studies, 2026)
This study aimed to examine the effectiveness of cooperative learning in enhancing students’ physical fitness components in physical education classes. A quasi-experimental design employing a pretest-posttest control group approach was used. A total of 32 students participated in the study and were divided into an experimental group (n = 16), which received cooperative learning instruction, and a control group (n = 16), which received conventional instruction. The physical fitness components assessed included flexibility, agility, muscular strength, speed, and balance. Data were collected through physical fitness tests administered before and after the intervention. Descriptive statistics, paired-samples t-tests, and independent-samples t-tests were used to analyze the data with the assistance of SPSS software. The findings revealed that the experimental group showed significantly greater improvements in all measured physical fitness components compared to the control group (p < 0.05). Cooperative learning enhanced students’ active participation, peer interaction, learning motivation, and opportunities for meaningful practice. These results indicate that cooperative learning is an effective instructional strategy for improving students’ physical fitness in physical education settings. Therefore, physical education teachers are encouraged to incorporate cooperative learning strategies into their instructional practices to maximize students’ physical and social development.